(3EQTGO GdWdGH Edi hSjdI GdMSGHs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s ((3GdeOQSI GdCTQajI s)
(3ChdgG (B:s
(3GdMeO ddg eSgd GdMSGH heghf GdUYGH CdN s
(3BNQgG (B:s
(3gPG BNQ eG jSQg Gddg ai gPG GdJYdjb s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
Keywords: (3GdQjGVjGJs